A Cross Sectional Study of Glycemic Status in Diabetics Taking Statins - Usama Ahmad, Muhammad Shahid Sharif, Ali Haider, Javeria Ghafoor, Adnan Salim Malik, Arz Muhammad, (Pakistan Journal of Medical & Health Sciences, 2023)
In this case research, an effort was made to analyze the diabetogenic statins effect, as well as the way this is associated with different comorbidities associated. Study Design: Cross-Sectional Study Place of Study: Punjab Institute of Cardiology Lahore. Duration of Study: October 2020 to March 2022 Materials and Methods: This cross-sectional study was conducted at the Department of Cardiology between October 2020 to March 2022 for duration of one year and Five months in order to collect the necessary data. Participants were required to have had normal blood sugar levels when they began taking statins and to have been on statins for at least one year prior to eligibility. Those who had never been diagnosed with diabetes mellitus were more likely to get the condition as a result of this study, according to the findings new Onset Diabetes Mellitus (NODM). Both the glucose and insulin concentrations in the blood were subjected to estimation. The subjects saw and reported additional adverse effects caused by statins and comorbidities associated with them. To meet the objective of analyzing adverse reactions to drugs, descriptive statistics were required. Result: The most commonly prescribed dosage for statins was 40mg of atorvastatin, according to the statistics. Diabetes was detected in roughly 25 percent of patients on 80mg of atorvastatin. Conclusion: The use of statins is related with a risk of non-alcoholic fatty liver disease ranging from low to significant (NODM). The amount of statin medication a person takes is one of the most influential contributors to the increase in diabetes risk linked with statin use. Keywords: Hyperglycemia, newly diagnosed diabetes, statins, and type 2 diabetes